Novel Genome-Editing Approaches for Developing Non-GM Crops for Sustainable Improvement and the Mitigation of Climate Changes - Naglaa A, Abdallah; Hamwieh, Aladdin; Baum, Michael (Springer Publishing Company, 2024)
The utilization of clustered regularly interspaced short palindromic repeat (CRISPR)/Cas-based genome-editing technologies holds significant promise in the realm of crop genome manipulation since it enables precise modifications and expedites the progress of crop breeding initiatives. Crop improvements need to be genetically stable and transgene-free to ensure sustainability, mitigate environmental stresses, and gain consumer and decision-maker acceptance. Edited plants with transgenic-based approaches can address many problems associated with transgenic plants. CRISPR/Cas genome editing allows the development of precise modification at the nucleotide level that is not different from that which occurred from natural recombination during conventional breeding. Various methods have accomplished genome editing without the incorporation of transgenes. These strategies involve the utilization of site-directed nucleases, specifically type 1 (SDN-1), as well as cisgenic editing employing SDN-2. A number of countries, including the United States, Japan, India, and Australia, classify genome-edited crops that lack transgenes or foreign deoxyribonucleic acid (DNA) as non-genetically modified (non-GM) and thereby exclude them from regulations governing genetically modified organisms (GMOs). Agrobacterium-mediated or biolistic transformations are often employed methods for introducing the CRISPR components into the plant genome. The first generation plants could be used to obtain transgenic-free plants through the segregation of heterozygous crops. However, the transformation process is expensive and time-consuming, and many species are recalcitrant to transformation. In addition, it will be impossible to get transgenic-free plants from plants that are propagated vegetatively. The target delivery of Cas-gRNA nucleoprotein using chemical or physical methods could be a promising tool for developing transgene-free edited plants. Also, viral vectors were used for the delivery of CRISPR/Cas components to obtain transgene-free edited plants. In a recent study, the technique of grafting was employed to introduce transgenic roots harboring tRNA-like sequences (TLS) that serve as molecular signals facilitating the transport of ribonucleic acids (RNAs) over long distances within plants. This approach was utilized to distribute the CRISPR/Cas components to both the shoots and seeds of the plants. This chapter presents a thorough examination of the many techniques employed in the acquisition of transgene-free plant genome editing, as well as the advancements made in comparison to other genetically modified (GM) plants and edited organisms.